Lessons from the analysis of nonhuman primates for understanding human aging and neurodegenerative diseases - Verdier, Jean-Michel; Acquatella, Isabelle; Lautier, Corinne; Devau, Gina; Trouche, Stéphanie; Lasbleiz, Christelle; Mestre-Francés, Nadine (Frontiers in Neuroscience, 2015)
Animal models are necessary tools for solving the most serious challenges facing medical research. In aging and neurodegenerative disease studies, rodents occupy a place of choice. However, the most challenging questions about longevity, the complexity and functioning of brain networks or social intelligence can almost only be investigated in nonhuman primates. Beside the fact that their brain structure is much closer to that of humans, they develop highly complex cognitive strategies and they are visually-oriented like humans. For these reasons, they deserve consideration, although their management and care are more complicated and the related costs much higher. Despite these caveats, considerable scientific advances have been possible using nonhuman primates. This review concisely summarizes their role in the study of aging and of the mechanisms involved in neurodegenerative disorders associated mainly with cognitive dysfunctions (Alzheimer's and prion diseases) or motor deficits (Parkinson's and related diseases).